Gender equality in couples and self-rated health - A survey study evaluating measurements of gender equality and its impact on health - Sörlin Ann; Lindholm Lars; Ng Nawi; Öhman Ann (International Journal for Equity in Health, 2011)
Abstract Background Men and women have different patterns of health. These differences between the sexes present a challenge to the field of public health. The question why women experience more health problems than men despite their longevity has been discussed extensively, with both social and biological theories being offered as plausible explanations. In this article, we focus on how gender equality in a partnership might be associated with the respondents' perceptions of health. Methods This study was a cross-sectional survey with 1400 respondents. We measured gender equality using two different measures: 1) a self-reported gender equality index, and 2) a self-perceived gender equality question. The aim of comparison of the self-reported gender equality index with the self-perceived gender equality question was to reveal possible disagreements between the normative discourse on gender equality and daily practice in couple relationships. We then evaluated the association with health, measured as self-rated health (SRH). With SRH dichotomized into 'good' and 'poor', logistic regression was used to assess factors associated with the outcome. For the comparison between the self-reported gender equality index and self-perceived gender equality, kappa statistics were used. Results Associations between gender equality and health found in this study vary with the type of gender equality measurement. Overall, we found little agreement between the self-reported gender equality index and self-perceived gender equality. Further, the patterns of agreement between self-perceived and self-reported gender equality were quite different for men and women: men perceived greater gender equality than they reported in the index, while women perceived less gender equality than they reported. The associations to health were depending on gender equality measurement used. Conclusions Men and women perceive and report gender equality differently. This means that it is necessary not only to be conscious of the methods and measurements used to quantify men's and women's opinions of gender equality, but also to be aware of the implications for health outcomes.